Keloid acne of the neck: epidemiological studies over 10 years. - ADEGBIDI, Hugues; Atadokpede, Felix; do Ango-Padonou, Florencia; Yedomon, Hounnakpon (My University, 2005)
Abstract Background Acne keloidalis nuchae is a chronic condition affecting young adult males of African origin. The frequency of the condition is low but its occurrence has a signiﬁcant impact on the patient’s quality of life. Patients and methods We performed a retrospective study on data collected over a period of 10 years in the Department of Dermatology and Venereology at the Centre National Hospitalier et Universitaire (CNHU) in Cotonou, Benin. We examined 90 ﬁles covering the period from 1993 to 2002 in terms of the epidemiologic, clinical and therapeutic features and course of the disease. Results The frequency of acne keloidalis nuchae in patients attending the department for consultations over this period was 0.7%. All patients were male, and their mean age was 29 years. The mean period between disease onset and initial consultation in the department was 29 months. Of the patients diagnosed, 82.22% were seen at the stage when the keloid lesions were small. Lesion size did not appear to depend on the duration of the disease. The mean duration of follow up for the 34 patients reviewed was 22 weeks. In nine cases the lesions had spread and in ﬁve cases they had resolved. The treatment proposed depended on the type of lesion, but no effective therapeutic guidelines exist. Conclusions The study has demonstrated that, once the clinical stage of purely inﬂammatory lesions has passed, delay in consultation has a negligible effect on the course of the disease, which remains chronic and recurrent. A preventive approach using Information Education Communication (IEC) would be preferable.
Keywords: Keloid acne; black; epidemiology; clinical aspects